Contextual determinants of generational continuation of female genital mutilation among women of reproductive age in nigeria: analysis of the 2018 demographic and health survey - Tosin Olajide Oni; David Aduragbemi Okunlola (BMC, 2024)
Abstract Background Female genital mutilation (FGM) has negative health implications and has long been recognised as violating sexual rights. Despite the huge efforts expended on eradicating FGM, generational continuation of the practice, i.e. the act of mutilated women also mutilating their daughters, persists in Nigeria. This study investigated the individual, household, and community factors associated with generational continuation of FGM among women in Nigeria. Methods The study analysed data from the 2018 Nigeria Demographic and Health Survey (NDHS). A weighted sample of 3835 women with FGM history and who had given birth to female children was analysed. Models were estimated using mixed-effects multilevel logistic regression with Stata 16.0. Results The results showed that 40.0% of women continued FGM for their daughters. Regional prevalence of FGM continuation ranged from 14.9% in the South-South (the lowest) to 64.3% in the North-West (the highest). Women aged 15-24 years (uaOR = 0.40; 95% CI:0.28-0.57) and rich (uaOR = 0.44; 95% CI:0.35-0.56) had the least likelihood of generational continuation of FGM. In communities with low proportions of women unexposed to the media, the likelihood of FGM continuation was significantly higher (uaOR = 1.85; 95% CI:1.35-2.53). Generational continuation of FGM was significantly lower in communities with moderate proportions of uneducated mothers (aOR = 0.6; 95% CI:0.42-0.86). Conclusion FGM continuation was high in Nigeria, and it was most common among older and poor mothers and in communities with large proportions of uneducated women and those unexposed to the media. Existing National Policy and Plan on FGM elimination should be strengthened to target these characteristics.